Land-cover patterns and hydrogeomorphology of tributaries: are these important stressors for the water quality of reservoirs in the Mediterranean region? - Palma, Patrícia (2020)
Four streams in the Guadiana watershed were followed up to assess hydrogeomorphological and physicochemical characteristics, and to analyze its correlation with land use/land cover (LULC), analyzing their possible influence in reservoir water quality and possible influence in the reservoir water quality. The highest amounts of organic descriptors and nutrients were quantified in streams with the major percentage of olive groves and vineyards and urban land cover classes. Streams more influenced by agro-silvo-pastoral class presented better water quality, as this type of LULC acts as a bu er of the contamination runo . The results highlighted that the hydrogeomorphology of the streams may influence the transfer of pollutants loads to reservoirs. Hence, in intermittent streams characterized by coarse particles in the sediment, high amounts of pollutants are accumulated when the flow ceases, and are further transported to the reservoirs when the flow retakes. On the contrary, streams with sediments characterized by a great percentage of fine particles and organic matter do not induce so much stress in reservoirs, since these allow the adsorption of nutrients and trace elements, without their transfer to reservoirs